Pengetahuan Mempengaruhi Stigma Tokoh Agama Terhadap Orang Dengan HIV/AIDS (ODHA) di Kabupaten Banyumas - Ratnawati, Misrina; Jati, Sutopo Patria; BM, Syamsulhuda (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2017)
Background: The rate of the spread of HIV/ AIDS that more and more worrisome needs an integrated tackling from various parties such as the government, non – governmental organizations, includes religious figures. Religious leader is believed that they have a strategic role in tackling the bad effect, at the same time break the chain of the spread of HIV and AIDS. This research aimed to know the factors that influence the stigma of religious figures towards people living with HIV/ AIDS.Method: The kind of the research isanalytical correlational with crossectional approach. The data was collected from 164 the religious figures. Data were analyzed using univariate with frequency distribution, bivariate with Chi-square, and multivariate with logistic regression.Result: The result showed that factors related to The stigma towards people living with HIV were knowledge about HIV/AIDS, value/belief and friend’s support. Knowledge about HIV/AIDS was the main factor that has considerable influence to The stigma towards people living with HIV. From this research, can be conclude that Knowledge about HIV/AIDS can affect The stigma towards people living with HIV besides value/belief and friend’s support.Keywords : The stigma towards people living with HIV, knowledge, religious figures